INDIVIDUAL’S CREATIVITY: INSTRUMENT ASSESSMENT AND VALIDATION IN THE CONTEXT OF MALAYSIAN HIGHER LEARNING INSTITUTION - Mat Nawi , Nur Ainatul Mardiah; Mohamad Rosman , Mohamad Rahimi; Md Arifin , Noor Arina; Mokhtar , Siti Aishah; Hamidon , Huda; Md Radzi , Salliza (Journal of Islamic, Social, Economics and Development, 2024)
The organizations have been forced to develop methods for improving their performance to achieve a competitive advantage in the market by the ever-increasing competition worldwide. Higher Education Institutions (HEIs) are no exception. The previous studies showed that there are contradicting findings between organizational culture versus individual creativity. Therefore, this study is conducted to explore the factors influencing individual creativity focusing on Higher Education Institutions in Malaysia. Hence, the objectives of this study are (1) to investigate the level of individual creativity among academician in Malaysia and (2) to investigate the relationship between individual creativity and its predictors (adhocracy culture, clan culture, market culture, and hierarchy culture) among academician in Malaysia. Based on the previous research, the predictors and dependent variables were adopted. Then, a pilot study was conducted. In order to validate the instrument, the expert review process was conducted. The face validity and reliability investigation of possible respondents was completed. As a result, an instrument with five variables and 71 items was created to measure individual creativity in the context of Higher Education Institutions (HEIs).